2009
DOI: 10.1111/j.1442-9071.2009.02152.x
|View full text |Cite
|
Sign up to set email alerts
|

Cataract in central Sri Lanka: cataract surgical coverage and self‐reported barriers to cataract surgery

Abstract: Cataract surgical coverage in central Sri Lanka is higher than that in neighbouring developing regions. Surgical uptake may be improved through better community education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
2
23
3
Order By: Relevance
“…20 Some factors should be considered in this regard. Similar to some studies, [21][22][23] we also believe that women's access to health services has improved in recent decades; therefore, younger women now utilize such services as men do. However, older women have less utilized health and medical care services.…”
Section: Discussionmentioning
confidence: 53%
“…20 Some factors should be considered in this regard. Similar to some studies, [21][22][23] we also believe that women's access to health services has improved in recent decades; therefore, younger women now utilize such services as men do. However, older women have less utilized health and medical care services.…”
Section: Discussionmentioning
confidence: 53%
“…Fear of surgery, including fear of poor surgical outcomes, was also one of the important reasons for not undergoing surgery, which is consistent with previous reports from China 14 and other developing countries. 13,20 Population-based studies have frequently demonstrated that outcomes of cataract surgery in rural China are suboptimal. 29 Therefore, establishing a system for training local doctors to perform high-quality cataract surgery is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to uptake of cataract surgery have been well-described in Africa 6,[9][10][11] and Asia, [12][13][14][15][16][17] and appear to include direct and indirect costs, 10,11,18,19 lack of knowledge, 13,20 fear of surgery, 13,20 concerns about the quality of services, 11,13 transportation problems, 12,15,16,21 and discrimination on the basis of sex and age. 12,15,16 Information on barriers to cataract surgery in China is sparse; barriers 14,17,19,22 include lack of knowledge, concern over poor quality of local services and cost of cataract surgery.…”
Section: Introductionmentioning
confidence: 96%
“…6 Over half (54.1%) of those who felt they needed eye care but did not use available services reported that they did not access services because they did not think their eye problem was important. 6 In population-based studies in Sri Lanka, 7 Guatemala 8 and Nepal, 9 subjects reported that fear and a lack of awareness of treatment for their vision loss were important barriers to accessing cataract treatment along with financial constraints, not having someone to accompany them to the surgery, and distance to the hospital.…”
Section: Introductionmentioning
confidence: 99%